Audit Sistem Informasi Manajemen Risiko pada PT. Sangsaka Catur Bersama Menggunakan Kerangka Kerja COBIT 5 - Florentina, Yulika; Rusdi, Ibnu (Smart Comp :Jurnalnya Orang Pintar Komputer, 2024)
The use of information systems in companies can facilitate the decision-making process while simplifying the information transfer process. This also increases the value of the company in the eyes of customers. The Cashier Application (AKSIR) is an information system used by PT Sangsaka Catur Bersama in the sales and inventory department. AKSIR has not taken any steps to evaluate whether the achievement of AKSIR objectives is in accordance with the business objectives of the company. Cobit 5 was chosen as a framework because it can be used by companies of all sizes focusing on domains EDM01, EDM02, EDM03, EMD04, APO01, APO02, APO07, APO12, and APO13. The purpose of the study was to assess whether the current information system meets the company's policy standards seen from the EDM and APO domains, determine the level of capability and gap value and provide recommendations to companies to improve the governance of their information systems. The results showed an average maturity level of 377% of the 9th subdomain into level F of the rating scale which indicates the achievement of Fully Achieved value, Sub domain APO01 has the largest gap from the expected target of -1.92 with an overall average gap of -0.22.